Natural wave propagation in mine environments. - Lienard, M. (IEEE Transactions on antennas and propagation)
Theoretical and experimental aspects of the natural propagation of high-frequency waves in mines are presented. A narrow-band and a wide-band analysis have been carried out to determine the most important characteristics of the channel such as the longitudinal attenuation, the coherence bandwidth, and the delay spread of the impulse response in the various areas of an underground mine. The basic principle of a localization of a mobile has also been checked by determining the direction of arrival of the waves